INVESTMENT ACTIVITY OF BANKS IN THE UKRAINIAN STOCK MARKET UNDER MARTIAL LAW AND CONDITIONS OF FINANCIAL INSTABILITY - Soroka, Rostyslav (Current Problems of Sustainable Development, 2026)
The article investigates the peculiarities of banks’ investment activity in the Ukrainian stock market under martial law and conditions of financial instability. The relevance of the study is determined by the transformation of the banking sector caused by large-scale military aggression, changes in macroeconomic conditions, increased financial risks, and the growing need for financing public expenditures through domestic borrowing instruments. The theoretical foundations of banks’ investment activity are examined, and the role of commercial banks as institutional investors in the capital market is substantiated. The study analyzes the dynamics of banking system assets, loan portfolios, investments in securities, and government bonds. Based on statistical data from the National Bank of Ukraine, the Ministry of Finance of Ukraine, and the National Securities and Stock Market Commission, it is established that the volume of banks’ investments in securities increased significantly during the analyzed period and became one of the key directions of asset allocation. The research proves that under martial law the investment component of banks’ active operations strengthened considerably, while investments in securities in certain years exceeded the volume of lending to customers. Special attention is paid to the participation of banks in the domestic government bond market. The findings indicate that banks have become the largest group of investors in domestic government bonds and play a crucial role in financing the state budget deficit. The study identifies the main problems affecting the development of banks’ investment activity, including excessive concentration of investments in government securities, insufficient development of the corporate segment of the stock market, crowding out of lending to the real sector of the economy, and limited participation of foreign investors. The paper substantiates prospective directions for improving the efficiency of banks’ investment activity, such as diversification of investment portfolios, development of the corporate securities market, attraction of foreign capital, enhancement of market infrastructure, and further digitalization of financial services.